Purification and determination of plant hormones auxin and abscisic acid using solid phase extraction and two-dimensional high performance liquid chromatography - Dobrev, P I; Havlícek, L; Vagner, M; Malbeck, J; Kamínek, M (Journal of chromatography. A, 2005)
A method for separation and purification of plant hormones auxin and abscisic acid based on mixed mode reversed-phase anion-exchange solid phase extraction and two-dimensional HPLC was developed. Two-dimensional HPLC in "heart cutting" mode was very efficient in the purification of these two hormones. Its purification power is high enough to allow reliable on-line quantification of both hormones even with non-selective detectors.
Keywords: kyselina abscisová; Reproducibility of Results; kyseliny indoloctové; Chromatography, High Pressure Liquid; Plant Growth Regulators; Indoleacetic Acids; Abscisic Acid; reprodukovatelnost výsledků; vysokoúčinná kapalinová chromatografie; regulátory růstu rostlin